JURIDICIAL IMPLICATIONS OF THE CONSTITUTIONAL COURT DECISION NUMBER 90/PUU-XXI/2023 IN THE PERSPECTIVE OF LEGAL SOCIOLOGY - M, Tina Diarti; Zukriadi, Diki (JCH (Jurnal Cendekia Hukum), 2024)
This study aims to examine the juridical implications of Constitutional Court Decision Number 90/PUU-XXI/2023 from the perspective of Legal Sociology. The issue of the obstruction of democracy due to conflicts of interest, aimed at maintaining political dynasties that indirectly reflect the practice of nepotism surrounds the decision, especially with the difference of opinion among the judges. This research is qualitative in nature and uses normative legal research methods, that rely on secondary data in the form of research results or journals. The results show that the Constitutional Court Decision No. 90/PUU-XXI/2023 which contains amendments to Law No. 17/2017 Article 169 letter q, which regulates the age limit for candidacy for president and vice president does not have a formal defect and does not conflict with the Judicial Power Law. However, this decision caused controversy because of the family relationship between the Chief Justice of the Constitutional Court and his nephew. From the perspective of legal sociology, the decision can be seen as a deviation from the principle of judicial independence that has the potential to create conflicts of interest and reduce public trust in the judicial system. In addition, this decision also exacerbates social inequality caused by political dynasties that utilize the law as a tool to maintain political dominance. The stifling of democracy is reflected in the limited public access to political processes and legal decisions, as well as the practice of nepotism that raises concerns about the logical consistency of decisions made quickly. Disagreements among judges, through dissenting and concurring opinions, indicate different values in interpreting the law.